Mobile Metal Ion and Spatiotemporal Hydrocarbon Analysis as mineral exploration tools – application to targets in Greenland - Halonen, Nina (My University, 2024)
Disko-Nuussuaq region in Western Greenland is a desired target for mineral exploration, as previous findings in the area indicate potential for Ni-Cu-PGE sulphide mineralization. The area is located in the North Atlantic Igneous Province (NAIP), a Large Igneous Province (LIP) which host numerous mineral deposits throughout the world, furthermore increasing the potential of a mineralization in the area. However, the northern and remote location of the area defines the ways in which mineral exploration is conducted. This thesis was set out to find if known geophysical anomalies in Disko-Nuussuaq are identified in a regional surface soil sampling survey. In 2019, a soil sampling survey was carried out for the purpose of mineral exploration. Sampling was conducted in eight areas, four of which are discussed in this thesis. These are located in the Kuugannguaq valley in Disko Island and the Aaffarsuaq valley in Nuussuaq Peninsula. In these four areas, a total of 1558 samples were collected and analysed with Mobile Metal Ion (MMI) and Spatiotemporal Geochemical Hydrocarbon (SGH) weak leach methods. Together with sampling, the sampling environment was logged during field work. From the results of MMI and SGH analyses, some suggested correlation between geophysical anomalies and patterns in the weak leach data was found. However, the varying responses between, and within, sample lines raise questions about the proper sampling for these specific methods. The sampling environment was changing as the topography of the valleys plays a large role in the moisture, vegetation and soil profile in each given sample point. These varying conditions can have an impact on the results of MMI and SGH methods. Overall, the sampling survey was successful and soil sampling for weak leach methods can be seen as a plausible option in environments such as Disko-Nuussuaq that require sensitive operation. Furthermore, based on results of this survey, is possible to indicate the most promising areas for future surveys.

Disko-Nuussuaq Länsi-Grönlannissa on kiinnostava malminetsintäkohde, sillä aikaisemmat löydöt alueella viittaavat mahdolliseen Ni-Cu-PGE sulfidimineralisaatioon. Alue on osa Pohjois-Atlantin magmaprovinssia (North Atlantic Igneous Province), mikä nostaa alueen mineralisaatiopotentiaalia, sillä tunnettuihin suuriin magmaprovinsseihin liittyy monia tunnettuja mineralisaatioita maailmanlaajuisesti. Kuitenkin Disko-Nuussuaqin syrjäinen sijainti, lyhyt kenttäkausi ja pohjoinen herkkä luonto rajoittavat malminetsintää ja tutkimusta. Tämän Pro Gradu-työn tarkoituksena on selvittää, voidaanko Disko-Nuussuaqin tunnetut geofysikaaliset anomaliat tunnistaa maaperägeokemiallisella pintamaanäytteenottotutkimuksella. Tutkimusaineisto on kerätty vuonna 2019 kahdeksalta alueelta, joista neljän tutkimustuloksia käsitellään tässä opinnäytetyössä. Tutkimuskohteet sijaitsevat Kuugannguaqin laaksossa Diskon saarella ja Aaffarsuaqin laaksossa Nuussuaqin niemimaalla. Näiltä neljältä alueelta kerättyjä näytteitä on 1558 ja ne on analysoitu Mobile Metal Ion (MMI) ja Spatiotemporal Geochemical Hydrocarbon (SGH) heikkouuttomenetelmillä. MMI- ja SGH-analyysien tuloksista löydettiin viitteitä maaperän alla oleviin geofysikaalisiin anomalioihin. Kuitenkin laaksojen vaihteleva topografia ja kosteusolosuhteet haastavat näytteenotolle sekä menetelmien luotettavuutta, minkä vuoksi myös näytteenottoprosessia sekä heikkouuttomenetelmien soveltuvuutta Disko-Nuussuaqisaa arvioitiin. Tulokset osoittavat tutkimuksen kuitenkin onnistuneen ja niiden perusteella voidaan osoittaa lupaavimmat alueet mahdollisille jatkotutkimuksille.
Keywords: Mineral exploration, weak leach methods, nickel, copper, Greenland, malminetsintä, heikkouuttomenetelmät, nikkeli, kupari, Grönlanti